SIMEON UROŠ PALAIOLOGOS, EMPEROR OF TRIKALA - Osswald, Brendan (Analecta Stagorum et Meteororum, 2022)
The present article presents the sources related to the political career of the King of Thessaly, Symeon Uroš Palaiologos, and subsequently refers to the phases of the life and actions of the Serbo-Byzantine ruler. Specifically, it discusses his youth in Serbia, his years as Despot of Epirus (ca. 1348-1356), his political activities in Serbia, and finally his establishment in Thessaly (from 1359 onwards), as well as his relationship with the regional rulers and those subordinate to him, such as Petros Liosas, Ioannis Spatas, and Thomas Preloubos in Epirus, Despot Ioannis Komnenos in southern Albania, and Radoslav Hlapenos in western Macedonia. Beyond these, the article examines various aspects of his reign, such as his imperial ideology, administration, religious policies, and the issue of the so-called "Serbocracy." Finally, it explores matters concerning his death and legacy.